2021
DOI: 10.1186/s12864-021-07958-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profile under abiotic stress of the barley non-specific lipid transfer protein gene family and its Qingke Orthologues

Abstract: Background Plant non-specific lipid transfer proteins (nsLTPs), a group of small, basic ubiquitous proteins to participate in lipid transfer, cuticle formation and stress response, are involved in the regulation of plant growth and development. To date, although the nsLTP gene family of barley (Hordeum vulgare L.) has been preliminarily identified, it is still unclear in the recently completed genome database of barley and Qingke, and its transcriptional profiling under abiotic stress has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…An increasing number of studies have shown that plant nsLTP genes play an important role in the response to biotic and abiotic stresses and in plant growth and development [ 11 , 18 , 21 , 23 , 25 , 28 , 29 , 31 ]. To date, with the availability and feasibility of plant reference genomes, the nsLTP gene family has been identified at the genome-wide level in various plant species, including Arabidopsis, Gossypium , sesame, cotton, wheat, potato, tomato, tobacco, barley, maize, cabbage and Chinese cabbage [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 58 , 59 , 60 , 61 ]. In this study, 283, 127, 151 and 106 nsLTP genes were identified in B. napus , B. rapa , B. oleracea and A. thaliana genomes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that plant nsLTP genes play an important role in the response to biotic and abiotic stresses and in plant growth and development [ 11 , 18 , 21 , 23 , 25 , 28 , 29 , 31 ]. To date, with the availability and feasibility of plant reference genomes, the nsLTP gene family has been identified at the genome-wide level in various plant species, including Arabidopsis, Gossypium , sesame, cotton, wheat, potato, tomato, tobacco, barley, maize, cabbage and Chinese cabbage [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 58 , 59 , 60 , 61 ]. In this study, 283, 127, 151 and 106 nsLTP genes were identified in B. napus , B. rapa , B. oleracea and A. thaliana genomes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the uniqueness of the set of genes responsible for the reproduction of LTP protein in cereals [ 45 , 46 ].…”
Section: The Beer’s “Head” Biomoleculesmentioning
confidence: 99%
“…Table 2 shows the total number of nsLTP gene families in the main cereal crops used in the brewing process [ 45 ]. The researchers noted differences between grain crops in the types of genes and the uniqueness of type E for dicotyledons, while barley LTPs are also deficient for types C and X.…”
Section: The Beer’s “Head” Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the bZIP TF family as related to starch synthesis has been reported [ 26 ]. Many other gene families have been well-documented in barley, such as xyloglucan endotransglucosylase/hydrolases ( XTH s) [ 27 ], non-specific lipid transfer proteins ( nsLTP s) [ 28 ], SQUAMOSA - promoter binding like ( SPL ) [ 29 ], and GRAS (named after the first three identified proteins within this family, GAI, RGA, and SCR) [ 30 ] gene families. However, there is no integrated database with large-scale multi-omics data for barley gene families.…”
Section: Introductionmentioning
confidence: 99%